Depressive symptoms in midlife: the role of reproductive stage. Issue 6 (June 2016) - Almeida, Osvaldo P.; Marsh, Kylie; Flicker, Leon; Hickey, Martha; Sim, Moira; Ford, Andrew
Abstract: Objective: The aim of the study was to determine the prevalence of depression among community-dwelling women in the premenopause, menopausal transition (MT), and postmenopause stage. We also sought to clarify the direct and indirect contribution of menopausal status on the risk of depression. Methods: Cross-sectional survey of 1, 612 women aged 45 to 55 years living in the Perth metropolitan region, who were recruited using a random sample of the electoral roll (voting is compulsory in Australia), was conducted. Women with clinically significant symptoms of depression had Patient Health Questionnaire (PHQ-9) scores of at least 10, and those with major depression, reported symptoms consistent with Diagnostic and Statistical Manual of Mental Disorders, 5th ed (DSM-5), criteria. We used past and current gynecological and reproductive data to classify women as premenopausal, undergoing the MT, and postmenopausal. Other study measures included age, place of birth, education, marital status, drinking habit, number of children, medical illnesses, and history of premenstrual syndrome, postnatal depression, and past depression or anxiety. We investigated the direct and indirect effect of reproductive status with mediation/modulation analysis. Results: Among the women included in the survey, 8.2%, 11.5%, and 13.0% of women in premenopause, MT, and postmenopause had PHQ-9 at least 10, whereas major depression was present in 2.2%, 3.4%, and 3.6% of them. Reproductive status did not affect the prevalence of major depression, but more postmenopausal than premenopausal women had PHQ-9 score equal to or greater than 10 ( P = 0.013). Compared with premenopausal women, MT was associated with a direct odds ratio (OR) 1.35 (95% confidence interval [CI] = 0.90, 2.01) and indirect OR 1.08 (95% CI = 0.92, 1.26) for PHQ-9 at least 10. Similarly, the direct and indirect effect of the postmenopause on the odds of PHQ-9 at least 10 was OR 1.31 (95% CI = 0.87, 1.98) and OR 1.29 (95% CI = 1.10, 1.52). Conclusions: The slight, but not significant, excess of depressive symptoms during MT and early postmenopause cannot be attributed to a direct effect of reproductive status.